2016
DOI: 10.4038/jnsfsr.v44i1.7977
|View full text |Cite
|
Sign up to set email alerts
|

Extraction and degradation of chlorophyll a and b from Alternanthera sessilis

Abstract: Abstract:The use of Alternanthera sessilis, which is commonly known as Mukunuwenna in Sri Lanka as a source of chlorophyll was examined. The extraction of chlorophyll was carried out using buffered 80 % (v/v) aqueous acetone. The optimum operating conditions such as solvent to A. sessilis ratio, extraction temperature and extraction time were found to be 5 mL/g, 50 °C and 45 minutes, respectively. The yield of chlorophyll a and chlorophyll b under these optimum operating conditions were 659 and 261 µg/g of A. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 33 publications
2
7
0
Order By: Relevance
“…The absorption spectra acquired from the C . schoenanthus leaves in this study was similar to that of chlorophyll (Figure ) …”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…The absorption spectra acquired from the C . schoenanthus leaves in this study was similar to that of chlorophyll (Figure ) …”
Section: Resultssupporting
confidence: 80%
“…Hence, as the polarity of the solvent decreased, it increased the solubility of the polar solvents. 37 In one study, Jinasena et al (2016) investigated the extraction of the organic dye molecules (chlorophyll) from Alternanthera sessilis under different temperatures. They noted that the natural dye molecules absorbance increases with increases of temperature.…”
Section: Effect Of Different Temperature Values On the Extraction Omentioning
confidence: 99%
“…A further increase in temperature over the optimum value was insignificant. The same observation was recorded in Reference [28]. The last parameter investigated was the mixing ratio.…”
Section: Main Effect Plotsupporting
confidence: 75%
“…has then been applied to calculate the chlorophyll contents. Also, it has been discussed by investigators that the turbidity in a solution can play a significant role in determination of chlorophyll content [14,30]. It has been suggested that for a clear solution absorbance at 750 nm should be near to zero and absorbance in the range of 510-550 nm should not be more than 10% of the major red peak absorbance [22] The absorbance values in the green and yellow region of the spectra have been observed to be less than 10% of the red peak absorbance.…”
Section: Rafas-2021mentioning
confidence: 99%